Role of Neuron-Specific Enolase in the Diagnosis and Disease Monitoring of Sarcoidosis - Noriaki Sunaga; Yasuhiko Koga; Yoshimasa Hachisu; Koichi Yamaguchi; Masaki Aikawa; Norimitsu Kasahara; Yosuke Miura; Hiroaki Tsurumaki; Masakiyo Yatomi; Reiko Sakurai; Toshitaka Maeno; Takeshi Hisada (Canadian Respiratory Journal)
Sarcoidosis is a systemic granulomatous disease of unknown etiology. The diagnosis of sarcoidosis is based on clinicopathologic findings accompanied by the formation of granulomas in multiple organs, including the lung. Although angiotensin-converting enzyme (ACE) and soluble interleukin 2 receptor (sIL-2R) are traditionally used for the diagnosis of sarcoidosis, specific diagnostic markers remain to be determined. In the current study, we found that serum neuron-specific enolase (NSE) levels were elevated in patients with sarcoidosis. Serum NSE levels were positively correlated with serum ACE and sIL-2R levels. The sensitivity of NSE alone was modest, but its combination with sIL-2R and ACE had the highest sensitivity compared to those of each single marker. When comparing serum NSE and pro-gastrin-releasing peptide (ProGRP) levels in SCLC patients with those in patients with sarcoidosis and nonsarcoidotic benign diseases, serum NSE could be used to distinguish SCLC from sarcoidosis and nonsarcoidosis by setting at a cutoff value of 17.0 ng/ml with a sensitivity of 73.5% and a specificity of 90.2%, which were comparable to those of ProGRP. Serum NSE levels were associated with organ involvement and were higher in sarcoidosis patients who had been treated with oral corticosteroid (OCS) than in those who had never received OCS therapies; there was a positive association between elevated serum NSE levels and OCS use. Increased concentrations of serum NSE in patients at the nonremission phase decreased after spontaneous remission, whereas serum NSE levels fluctuated in accordance with serum ACE or sIL-2R levels during the follow-up period in patients with sarcoidosis. These findings suggest that NSE could be a marker for the diagnosis and monitoring of the clinical outcome of patients with sarcoidosis.